A 10-Year Clinical Analysis of Fungal Keratitis at CHUSJ - João Tiago Fernandes Loja (2020)
Purpose: To determine the microbiological profile, risk factors, treatment and surgical intervention rates of fungal keratitis at a tertiary referral center. Methods: A retrospective review of medical records from hospitalised patients treated for fungal keratitis at CHUSJ from 2009 to 2019 was conducted. Results: Overall, 43 patients were included in our study, being the majority aged over 65 years old (60.5%) and 46.5% were men. From the isolates cultured, 21 (48.8%) were filamentous forms and 22 (51.2%) were yeast forms. Candida species (n = 20, 46.5%), Fusarium species (n = 10, 23.3%), Aspergillus species (n = 4, 9.3%) were the most common isolated species. The most common risk factors were contact lens use (n=24,55.8%), history of keratitis (n=16,37.2%), and previous keratoplasties (n=14,32.6%). The most frequent use treatment was voriconazole, amphotericin B, fluconazole and fortified drops. Twenty-four cases (55.8%) required surgical intervention, of which 23 cases underwent therapeutic PKP. Ocular complications, such as evisceration was noted in 12 patients (27.9%) and endophthalmitis in 5 (11.6%). No statistically significant changes at BCVA were founded after treatment (p=0.687). When comparing the subgroups of filamentous fungi and yeast fungi, there were no statistically significant differences at the studied variables. Conclusion: Most patients with fungal keratitis have associated risk factors. Filamentous and yeast species had equally prevalent etiologies. In general, our results mirror the difficult task of treating fungal keratitis and reflect the bad outcomes obtained. Therefore, similar studies should be performed in order to formulate better diagnosis and treatment strategies, hence, to improve patients' outcome in the future.